2018
DOI: 10.1590/0004-282x20180053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity among stroke patients in five Brazilian cities: a cross-sectional study

Abstract: Objective: There is gap in knowledge about obesity prevalence in stroke patients from low-and middle-income countries. Therefore, we aimed to measure the prevalence of overweight and obesity status among patients with incident stroke in Brazil. Methods: In a crosssectional study, we measured the body mass index (BMI) of ischemic and hemorrhagic stroke patients. The sample was extracted in 2016, from the cities of Sobral (CE), Sertãozinho (SP), Campo Grande (MS), Joinville (SC) and Canoas (RS). Results: In 1,25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
2
4
0
4
Order By: Relevance
“…However, on the basis of the gender distinction results in this study, the detection rate of women at high risk is slightly higher than that of men. A study in Brazil showed that the exposure rate of the risk factors for stroke in overweight people is 40% higher than that of people with normal BMI (31). Although the exposure rate of smoking in the male population at high risk of stroke was found in this study to be much higher than that of women, the exposure rates of hypertension, diabetes, dyslipidemia, and obvious overweight or obesity risk factors in the high-risk female population were demonstrated significantly higher than those of men, which was speculated to be the cause of the higher detection rate in the female population in Zunyi, suggesting that more attention should be paid to general health education for female residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of the gender distinction results in this study, the detection rate of women at high risk is slightly higher than that of men. A study in Brazil showed that the exposure rate of the risk factors for stroke in overweight people is 40% higher than that of people with normal BMI (31). Although the exposure rate of smoking in the male population at high risk of stroke was found in this study to be much higher than that of women, the exposure rates of hypertension, diabetes, dyslipidemia, and obvious overweight or obesity risk factors in the high-risk female population were demonstrated significantly higher than those of men, which was speculated to be the cause of the higher detection rate in the female population in Zunyi, suggesting that more attention should be paid to general health education for female residents.…”
Section: Discussionmentioning
confidence: 99%
“…Una vez asociada con países de altos ingresos, la obesidad ahora también prevalece en países de bajos y medianos ingresos (15) . En adultos, el riesgo de ACV aumenta casi linealmente a partir de un IMC de 20, y los adultos con un IMC > 30 kg/m 2 tienen un riesgo 70 % mayor de ACV en comparación con pacientes con un IMC < 25 kg/m 2 (16) .…”
Section: Discussionunclassified
“…No Brasil, 80% dos casos no Brasil de AVC são classificados como AVC isquêmicos, demonstrando a importância epidemiológica no país, resultando na primeira causa de morte no Brasil, além de ser a segunda causa de perdas cognitivas (OLIVEIRA-FILHO et al, 2012;VICENTE et al, 2018).…”
Section: Introductionunclassified